Review of acute kidney injury and progression to chronic kidney disease in pediatric patients undergoing hematopoietic cell transplant - Vuong, Kim T.; Joseph, Catherine; Angelo, Joseph R. (Frontiers in Oncology, 2023)
While acute kidney injury (AKI) after hematopoietic cell transplant (HCT) has been well-described in pediatric patients, literature regarding the long term renal consequences of HCT-related AKI, the development of chronic kidney disease (CKD), and CKD care in pediatric patients post-HCT is limited. CKD affects almost 50% of patients after HCT with multifactorial etiology including infection, nephrotoxic medications, transplant-associated thrombotic microangiopathy, graft-versus-host disease, and sinusoidal obstruction syndrome (Rao 2005). As renal function declines in CKD, eventually progressing to end stage kidney disease (ESKD), mortality increases and is more than 80% among patients requiring dialysis (Parikh and Coca 2006; Zager et al. 1989). Using society guidelines and current literature, this review summarizes definitions and etiologies of and management strategies among patients with AKI and CKD post-HCT with an emphasis on albuminuria, hypertension, nutrition, metabolic acidosis, anemia, and mineral bone disease in patients with CKD. The goal of this review is to aid early identification and intervention in patients with renal dysfunction prior to development of ESKD, and to discuss ESKD and renal transplant in these patients post-HCT.